Chaos Suppression in Optically Injected Semiconductor Lasers Through an Unequally Spaced Optical Frequency Comb - Najm M. Al-Hosiny (Photonics)
This study theoretically investigates the impact of comb spacing irregularity on the dynamics of optically injected semiconductor lasers using a rate equation model. Bifurcation analysis, time-domain simulations, spectral properties, and Mode Suppression Ratio (MSR) calculations reveal that equal spacing induces strong mode competition and chaos, while unequal spacing suppresses chaos and enhances stability. Interestingly, the Flipped comb exhibits similar behavior to the unequal comb, further supporting the conclusion that relative spacing—not spectral order—governs stability the Arbitrary combs, though lacking structured spacing, demonstrate intermediate suppression, indicating that breaking uniformity mitigates instability, but optimal spacing maximizes stabilization. Extending beyond previous studies on frequency comb injection, this work identifies spacing irregularity as a key mechanism for chaos control, offering new strategies for laser stabilization in optical communications and photonic integration.